Severe Low Vitamin B12 Levels with Macrocytosis and Associated Hemolytic Anemia, Mimicking Thrombocytopenic Thrombotic Purpura: A Case Report and Literature Review (London Journal of Medical and Health Research, 2025)
The typical presentation of cobalamin deficiency is macrocytic anemia with or without neurologic symptoms, adding that the most frequent cause is Pernicious anemia, an autoimmune disease. We present a case of a 61year-old man with neurologic symptoms, pancytopenia, and laboratory findings consistent with hemolytic microangiopathic anemia (MAHA), like Thrombocytopenic Thrombotic Purpura (TTP). The lack of response to plasma exchange (PEX) therapy, concomitant with low plasma levels of cobalamin, low reticulocyte count, macrocytosis and remarkably high lactic dehydrogenase (LDH) levels made us suspect a pseudo-Thrombotic Microangiopathy (Pseudo TMA). The diagnosis was confirmed with a normal serum ADAMPTS13 activity and a rapid clinical and laboratory improvement after cobalamin supplementation. We think the internist must know the wide variety of presentations of Cobalamin deficiency, since it is a reversible cause of bone marrow failure, and its misdiagnosis may result in unnecessary costly procedures.
Keywords: Multiple Trauma; Accidents; Emergency Medicine.; secondary glaucoma; uveitis; posner-schlossman syndrome; intraocular pressure; topical corticosteroids.; plasma exchange; Vitamin B12; pernicious anemia; pseudo thrombotic microangiopathy; thrombocytopenic thrombotic purpura